Pre-Trial As Investigation Process Control System - Bauw, Lily; Silambi, Erni Dwita; Kama, Ibrahim; Ismail, Nurwita (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Pretrial is the initial thought to carry out supervisory actions against law enforcement officials so that in carrying out or carrying out their duties there is no abuse of authority.Purposes of the Research: To review and analyze Pre-Trial As Investigation Process Control System.Methods of the Research: The research method used in this study is Empirical Juridical law research with the reason that the author wants to examine norms related to pretrial and seek information directly about the implementation of pretrial at the Merauke Merauke Police.Results of the Research: Pretrial is a form of control both from superiors (Vertical) as well as from fellow law enforcers or third parties, namely the attorneys of suspects, suspects and their families (Horizontal) to see that the arrest, detention and determination of suspects are in accordance with applicable rules and pretrial. must have rules regarding inspection techniques so that there is uniformity.